POLITICAL COMMUNICATION AND THE POWER OF SOCIAL NETWORKS IN NATIONAL CRISES - Jevtović, Ana (National interest, 2025)
This research focuses on social networks and their role as activists during political crises within nation-states. Demonstrations and other forms of civil protest become more expressive with increased media coverage, where specific political demands are often hidden under the guise of non-violence. The author identifies five characteristic phases of message creation that, through various digital formats and modalities, contribute to increased visibility in the traditional public sphere. This amplifies the crisis's intensity, increasing the risk of escalation and internationalization. The nation-state and social networks are often incompatible during times of crisis, resulting in divided public opinion over possible solutions and their consequences. In a networked society, this leads to increased production of fear and moral panic, along with the spread of fake news, disinformation, and rumors. These dynamics can result in numerous incidents and further mobilization of youth, who represent a particularly vulnerable group. The new audience is increasingly overlapping, polarizing, shifting, and restructuring in accordance with changed social contexts and a digital environment that enables actor anonymity. Media technology, through digitalization and artificial intelligence, is becoming a conditio sine qua non for managing specific spaces and political relationships within a community, which also means that the course of action during crises is changing.
Keywords: political communication; social networks; propaganda; algorithms; trolls; moral panic; national crises related to color revolutions